Determinan Indeks Pembangunan Manusia: Analisa Pendekatan Maqāṣid SyarῙ’ah Al-Ghazali: Studi Kasus: Negara-Negara Oki - Mohammad Bintang P; Nurizal Ismail dan Indra (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
The multidimensional poverty is one of the big problems faced by some countries. It is a condition of an individual that had a low income, low education and low health care. Then, Amartya Sen and Mahbub Ulhaq had offered a new measure on Development namely Human Development Index (HDI). As in Islam, the development had arranged from the approach of Maqāṣid Syarῑ’ah and Al-Ghazali (1111 H) was the first Muslim intellectual who had Developed the thesis and had divided maqasid into three aspects, ḍaruriyyah, ḥajiyah, taḥsiniyyah. Furthermore, ḍaruriyyah consist of five basic elements namely Ḥifẓ Dῑn (Religion), Ḥifẓ Nafs (Life), Ḥifẓ ‘Aql (Intellectual), Ḥifẓ Nasl (Progeny), Ḥifẓ Māl (Wealth). Therefore the aim of the study was to search how the Maqāṣid Syarῑ’ah contributed to Human development theory and what were the factors of HDI of Maqāṣid Syarῑ’ah of Al-Ghazali approach. The Study selected 37 OIC Countries for eight years by using Data panel regression. The Study Showed that Ḥifẓ ‘Aql (Intellectual) and Ḥifẓ Māl (Wealth) has significant impat on HDI. On the other hand, Ḥifẓ Nafs (Life) Ḥifẓ Nasl (Progeny) have significant impact on HDI. This may due to the quality of Human Resources and Bureaucracy in Some OIC Countries. Meanwhile, the theory of Maqāṣid Syarῑ’ah had been developed well into Human Development but still had a lot of points to be evaluated.